Preserving cultural heritage: Integrating traditional values and local arts for sustainable tourism - Novita, Asti Amelia; Ngindana, Rispa; Putra, Endry (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2024)
Tourism significantly contributes to global economics, with Indonesia relying heavily on this sector for economic growth. However, tourism often challenges cultural and environmental preservation. This study explores the Cultural Village of Polowijen in Malang City, Indonesia, where Malangan masks play a central cultural and economic role. By integrating sustainable tourism principles, the research aims to develop a model for preserving Malangan masks, boosting economic growth while safeguarding cultural heritage. The study employs a qulitative approach. Joint Ministerial Regulation (PBM) Number 40 of 2009, which provides guidelines for cultural preservation through protection, development, and fostering, underpins the study. Findings indicate that sustainable tourism practices significantly contribute to both economic benefits and cultural preservation. Increased local engagement and awareness have been observed, with community members showing a strong commitment to preserving Malangan masks. Economic data reveal that cultural tourism development generates additional income and new employment opportunities. The regulation's implementation has successfully protected cultural heritage, enriched traditional arts, and promoted community sustainability. This study demonstrates that sustainable tourism can balance economic growth and cultural preservation, providing a model for other regions aiming to develop cultural tourism while safeguarding heritage.